1979
DOI: 10.1037/h0077589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differential interference with postnatal cerebellar neurogenesis on motor performance, activity level, and maze learning of rats: A developmental study.

Abstract: The region of the cerebellum was X-irradiated in infant rats with selected exposure schedules designed to produce animals in which the cerebellar cortex was (a) essentially normal except for agenesis of late forming granule cells with axons situated in the uppermost molecular layer (12-15X), (b) lacking in stellate cells, with a severe reduction in granule cells with axons in the upper molecular layer (8-15X), (c) morphologically disorganized but had only intermediate cell agenesis (4-5X), or (d) disorganized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(37 citation statements)
references
References 37 publications
2
34
0
1
Order By: Relevance
“…These are precisely the class of deficits that characterize decompositions and failures of associated movements. The present results suggest that, in addition to the motor coordination aspects of cerebellar function, one must also consider what Pellegrino and Altman (1979) have termed its "action coordination functions"-functions that relate to the integration of patterns of behavior.…”
Section: The Modulatory Role Of the Cerebellum And The Consequences Omentioning
confidence: 83%
See 1 more Smart Citation
“…These are precisely the class of deficits that characterize decompositions and failures of associated movements. The present results suggest that, in addition to the motor coordination aspects of cerebellar function, one must also consider what Pellegrino and Altman (1979) have termed its "action coordination functions"-functions that relate to the integration of patterns of behavior.…”
Section: The Modulatory Role Of the Cerebellum And The Consequences Omentioning
confidence: 83%
“…Spontaneous alternation between opposing responses (such as turning left vs. turning right) is highly characteristic of the normal exploratory behavior of animals (Dember & Fowler, 1958). Pellegrino and Altman (1979), however, report that animals with cerebellar agenesis fail to show this normal pattern of response alternation. Moreover, while these animals can acquire numerous complex maze habits as readily as normal animals, they are greatly impaired when the maze is configured so as to require the serial alternation between right and left turns.…”
Section: The Modulatory Role Of the Cerebellum And The Consequences Omentioning
confidence: 99%
“…Pellegrino and Altman (1979) suggested that in the apical domain of Purkinje cells, coordination of action takes place. High synaptic density of parallel fiber synapses, tagether with thick and numerous spiny branchlets and spines with extremely thin stalks, would explain the very large logical capacities of Purkinje cells in lobule VIa (Shepherd 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation of the cerebellum has multiple effects on its development, including reduction of the overall size, foliar/ lobular malformations [11,12], and functional deficiencies such as tremor, ataxia, hypoactivity, and cognitive deficits [13][14][15][16][17]. Populations of NSCs orchestrate the specification and patterning of the cerebellum.…”
Section: Introductionmentioning
confidence: 99%